2017
DOI: 10.1073/pnas.1700939114
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal T-cell receptor signaling compromises protein translation, ribosome biogenesis, and proliferation of mouse CD8 T cells

Abstract: Global transcriptomic and proteomic analyses of T cells have been rich sources of unbiased data for understanding T-cell activation. Lack of full concordance of these datasets has illustrated that important facets of T-cell activation are controlled at the level of translation. We undertook translatome analysis of CD8 T-cell activation, combining polysome profiling and microarray analysis. We revealed that altering T-cell receptor stimulation influenced recruitment of mRNAs to heavy polysomes and translation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 60 publications
2
60
0
Order By: Relevance
“…To explore the significance of the observed increase in RP gene expression in miR‐132 −/− CD4 + T cells, we analysed published transcriptional profiles of in vitro ‐generated Th1 and Th2 cells and found that CD4 + T cell activation results in a statistically significant shift towards global up‐regulation of RP gene levels (Figs H and EV1C). Taken together with previous reports demonstrating that activation of ribosome biosynthesis is associated with activation of CD8 + T cells and production of cytokines by CD4 + T cells in vitro , our findings suggested that the observed RP gene up‐regulation in miR‐132 −/− CD4 + T cells was a signature of enhanced activation.…”
Section: Resultssupporting
confidence: 88%
“…To explore the significance of the observed increase in RP gene expression in miR‐132 −/− CD4 + T cells, we analysed published transcriptional profiles of in vitro ‐generated Th1 and Th2 cells and found that CD4 + T cell activation results in a statistically significant shift towards global up‐regulation of RP gene levels (Figs H and EV1C). Taken together with previous reports demonstrating that activation of ribosome biosynthesis is associated with activation of CD8 + T cells and production of cytokines by CD4 + T cells in vitro , our findings suggested that the observed RP gene up‐regulation in miR‐132 −/− CD4 + T cells was a signature of enhanced activation.…”
Section: Resultssupporting
confidence: 88%
“…We performed a differential expression analysis to compare each activated cluster to the resting cells. Cells in the early stages of activation primarily increased expression of genes involved in immune and regulatory processes, whereas cells in the later stages of activation showed strong upregulation of genes involved in metabolic and biosynthetic functions (Supplementary Table 1), which are critical for T cell effector differentiation32,33. We then examined genes differentially expressed in the early activation cluster compared to both the resting and late activation clusters to identify transient early expression changes.…”
Section: Resultsmentioning
confidence: 99%
“…We cultured all cells in equivalent concentrations of exogenous IL-2, as this cytokine is required for T cells to enter the cell cycle and proliferate. Given that IL-2 production varies with stimulation strength33, addition of exogenous IL-2 enabled us to identify intrinsic changes in gene activation that were dependent solely on stimulation strength (Supplementary Fig. 2a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of ribosome biogenesis and protein translation is known to inhibit CD8 + T cell proliferation ( 35 ) and promote caspase-dependent cell death ( 36 ). We consistently observed decreased cell numbers under “T C 2” conditions (see Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%